The Developer's Dilemma: Structural Transformation, Inequality Dynamics, and Inclusive Growth - Armida Salsiah Alisjahbana; Kunal Sen; Andy Sumner; Arief Yusuf (Oxford University Press, 2022)
This book explores this developer's dilemma or 'Kuznetsian tension' between structural transformation and income inequality. Developing countries are seeking economic development—that is, structural transformation—which is inclusive in the sense that it is broad-based and raises the income of all, especially the poor. Thus, inclusive economic growth requires steady, or even falling, income inequality if it is to maximize the growth of incomes at the lower end of the distribution. Yet, this is at odds with Simon Kuznets hypothesis that economic development tends to put upward pressure on income inequality, at least initially and in the absence of countervailing policies. The book asks: what are the types or 'varieties' of structural transformation that have been experienced in developing countries? What inequality dynamics are associated with each variety of structural transformation? And what policies have been utilized to manage trade-offs between structural transformation, income inequality, and inclusive growth? The book answers these questions using a comparative case study approach, contrasting nine developing countries while employing a common analytical framework and a set of common datasets across the case studies. The intended intellectual contribution of the book is to provide a comparative analysis of the relationship between structural transformation, income inequality, and inclusive growth; to do so empirically at a regional and national level; and to draw conclusions from the cases on the varieties of structural transformation, their inequality dynamics, and the policies that have been employed to mediate the developer's dilemma.
Keywords: 330; structural transformation; Kuznetsian tension; economic growth; income inequality; developing countries